การพัฒนาแนวทางการนิเทศแบบสอนแนะสำหรับครูคณิตศาสตร์ สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษากาฬสินธุ์ เขต 3 - นนทะมาตย์, กฤติพร; จันทร์ศิริสิร, พชรวิทย์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 4 No 2 (2567): พฤษภาคม – สิงหาคม 2567, 2023)
การวิจัยนี้มีวัตถุประสงค์ 1) เพื่อศึกษาสภาพปัจจุบัน สภาพที่พึงประสงค์ และความต้องการจำเป็นของการนิเทศแบบสอนแนะสำหรับครูคณิตศาสตร์ สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษากาฬสินธุ์ เขต 3 2) เพื่อพัฒนาและประเมินแนวทางการนิเทศแบบสอนแนะสำหรับครูคณิตศาสตร์  สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษากาฬสินธุ์ เขต 3 เป็นการวิจัยแบบผสมผสาน  กลุ่มตัวอย่าง คือ ผู้บริหารสถานศึกษาและครูคณิตศาสตร์ จำนวน 196 คน การสัมภาษณ์ผู้บริหารสถานศึกษาและครูคณิตศาสตร์ จากโรงเรียนที่มีวิธีปฏิบัติดี จำนวน 6 คน ใช้เป็นแนวทางยกร่างและตรวจสอบยืนยันประเมินการพัฒนาการนิเทศแบบสอนแนะสำหรับครูคณิตศาสตร์ โดยผู้ทรงคุณวุฒิ 7 คน เครื่องมือที่ใช้ในการวิจัยเป็นแบบสอบถาม แบบสัมภาษณ์แบบมีโครงสร้าง  แบบประเมินความเหมาะสมและความเป็นไปได้ของแนวทางสถิติที่ใช้ในการวิเคราะห์ คือ ค่าเฉลี่ย  ร้อยละ ส่วนเบี่ยงเบนมาตรฐาน และค่าดัชนีความต้องการจำเป็น ผลการวิจัยพบว่า 1. สภาพปัจจุบันการนิเทศแบบสอนแนะสำหรับครูคณิตศาสตร์โดยรวมอยู่ในระดับปานกลาง สภาพที่พึงประสงค์ของการนิเทศแบบสอนแนะสำหรับครูคณิตศาสตร์โดยรวมอยู่ในระดับมากที่สุด ความต้องการจำเป็นของแนวทางการนิเทศแบบสอนแนะสำหรับครูคณิตศาสตร์ เรียงลำดับจากมากไปหาน้อยดังนี้ ด้านการปฏิบัติตามแผนการสอนแนะ ด้านการวางแผนการสอนแนะ ด้านการประเมินและติดตามผลการสอนแนะ และด้านการเตรียมการก่อนสอนแนะ 2. แนวทางการนิเทศแบบสอนแนะสำหรับครูคณิตศาสตร์ประกอบด้วย  ด้านการเตรียมการก่อนสอนแนะ มี 5 แนวทาง ด้านการวางแผนการสอนแนะ มี 3 แนวทาง ด้านการปฏิบัติตามแผนการสอนแนะ    มี 4 แนวทาง ด้านการประเมินและติดตามผลการสอนแนะ มี 5 แนวทาง  มีผลการประเมินความเหมาะสมโดยรวมอยู่ในระดับมากที่สุดและความเป็นไปได้ของแนวทางโดยรวมอยู่ในระดับมาก This research aimed 1) to study desirable present conditions and requirements of supervision of coaching teaching for mathematics teachers under Kalasin Primary Educational Service Area 3, 2) to develop and evaluate the guidelines of supervision of coaching teaching for mathematics teachers under Kalasin Primary Educational Service Area 3. For the method of the study, mixed methods research design was used. For the sample, it consisted of 196 school administrators and mathematics teachers. The interview of 6 school administrators from schools with the best practice was utilized to a guideline for 7 experts so as to draft, verify, and evaluate the development of instructional supervision for mathematics teachers. The questionnaire and the structured interview form and the appropriateness and feasibility assessment form of the approach were applied as the research instrument. Mean, percentage, standard deviation, and the required index value were taken as the statistics used for analysis. The results Showed that: 1. In the present condition, the overall level of the desirable present conditions and requirements of supervision of coaching teaching for mathematics teachers under Kalasin Primary Educational Service Area 3 was moderate. The desirable condition of supervision of coaching teaching for mathematics teachers was the highest level. The level of requirements or needs of supervision of coaching teaching for mathematics teachers could be ordered from high to low; as follows, on the implementation of the teaching plan, teaching planning, assessment and follow-up of instructional results, and preparation prior to instruction, respectively. 2. The guidelines of supervision of coaching teaching for the mathematics teachers comprised 5 guidelines in terms of preparation before teaching, 3 guidelines in terms of coaching-teaching plan, 4 guidelines regarding the implementation of the coaching-teaching plan, and 5 guidelines regarding the assessment and follow-up of teaching of coaching. The overall level of the suitability assessment result was at the highest, and the probability level was high.